Erectile Dysfunction Is Common among Men with Acromegaly and Is Associated with Morbidities Related to the Disease. (4th March 2015) - Lotti, Francesco; Rochira, Vincenzo; Pivonello, Rosario; Santi, Daniele; Galdiero, Mariano; Maseroli, Elisa; Balestrieri, Antonio; Faustini‐Fustini, Marco; Peri, Alessandro; Sforza, Alessandra; Colao, Annamaria; Maggi, Mario; et al.
Abstract Introduction The prevalence of erectile dysfunction (ED) and its correlates in men with acromegaly has never been investigated. Aim The aim of this study was to evaluate sexual function in men with acromegaly. Methods Multicenter‐based, retrospective analysis of a nonselected series of 57 acromegalic subjects (mean age: 52.7 ± 14.2 years) was performed. Acromegalic subjects reporting ED (n = 24) were compared with matched ED patients without acromegaly or pituitary disease (controls), selected from a cohort of more than 4, 000 subjects enrolled in the Florence Sexual Medicine and Andrology Unit. Main Outcome Measures Patients were interviewed using Structured Interview on Erectile Dysfunction (SIEDY) structured interview, a 13‐item tool for the assessment of ED‐related morbidities. Several clinical and biochemical parameters were taken. Penile color Doppler ultrasound (PCDU) was performed in a subgroup of 37 acromegalic subjects. Results ED was reported by 42.1% of acromegalic subjects. After adjusting for age and testosterone, acromegalic subjects with ED had a higher prevalence of hypertension and more often reported an impairment of sleep‐related erections and a longer smoking habit. Accordingly, acromegaly‐associated ED was characterized by a higher organic component and worse PCDU parameters. No relationship between ED and testosterone levels or other acromegaly‐related parameters was found. However, acromegalic subjects with severe ED reported a longer disease duration. In a case‐control analysis, comparing acromegalic subjects with ED‐matched controls free from acromegaly (1:5 ratio), acromegalic men had a worse ED problem and a higher organic component of ED, as derived from SIEDY score. In line with these data, acromegalic patients with ED had a higher prevalence of major adverse cardiovascular events history at enrollment and lower PCDU parameters. Conclusions Subjects with complicated acromegaly are at an increased risk of developing ED, especially those with cardiovascular morbidities. Our data suggest including a sexual function evaluation in routine acromegaly follow‐up. Lotti F, Rochira V, Pivonello R, Santi D, Galdiero M, Maseroli E, Balestrieri A, Faustini‐Fustini M, Peri A, Sforza A, Colao A, Maggi M, and Corona G. Erectile dysfunction is common among men with acromegaly and is associated with morbidities related to the disease. J Sex Med 2015;12:1184–1193.